Echoes from Dharamsala : music in the life of a Tibetan refugee community - Diehl, Keila (University of California Press, 2002)
In this book, Keila Diehl uses music to understand the experiences of Tibetans living in Dharamsala, a town in the Indian Himalayas that for more than 40 years has been home to Tibet's government-in-exile.